2018
DOI: 10.1002/jcc.25164
|View full text |Cite
|
Sign up to set email alerts
|

Predicting reduction potentials of 1,3,6‐triphenyl fulvenes using molecular electrostatic potential analysis of substituent effects

Abstract: The influence of mono- and multiple substituent effect on the reduction potential (E ) of 1,3,6-triphenyl fulvenes is investigated using B3LYP-SMD/6-311+G(d,p) level density functional theory. The molecular electrostatic potential (MESP) minimum at the fulvene π-system (V ) and the change in MESP at any of the fulvene carbon atoms (ΔV ) for both neutral and reduced forms are used as excellent measures of substituent effect from the para and meta positions of the 1,3 and 6-phenyl moieties. Substitution at 6-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…176 Extension of such studies to organic systems showed that the influence of mono-and multiple-substituent effects on the reduction potential (E 0 ) of 1, 3, 6-triphenyl fulvenes can be predicted by MESP V min at the fulvene π-system or by MESP at any of the fulvene carbon atoms (V C ). 177 This study also showed that significant change in E 0 occurs when the substituent at para-position of 6-phenyl unit is changed, compared any other positions. Recently, MESP features have been used to study the ground state as well as the absorption-emission properties of a series of 5-phenyl tris(8-hydroxyquinolinato) M(III) complexes (M = Al, Ga, In).…”
Section: Mesp As An Electronic Parametermentioning
confidence: 55%
See 1 more Smart Citation
“…176 Extension of such studies to organic systems showed that the influence of mono-and multiple-substituent effects on the reduction potential (E 0 ) of 1, 3, 6-triphenyl fulvenes can be predicted by MESP V min at the fulvene π-system or by MESP at any of the fulvene carbon atoms (V C ). 177 This study also showed that significant change in E 0 occurs when the substituent at para-position of 6-phenyl unit is changed, compared any other positions. Recently, MESP features have been used to study the ground state as well as the absorption-emission properties of a series of 5-phenyl tris(8-hydroxyquinolinato) M(III) complexes (M = Al, Ga, In).…”
Section: Mesp As An Electronic Parametermentioning
confidence: 55%
“…The MESP analysis at the chromium nucleus ( V Cr ) was very effective for making predictions on the redox properties of the Fischer carbene complexes (FCCs) of chromium 176 . Extension of such studies to organic systems showed that the influence of mono‐ and multiple‐substituent effects on the reduction potential ( E 0 ) of 1, 3, 6‐triphenyl fulvenes can be predicted by MESP V min at the fulvene π ‐system or by MESP at any of the fulvene carbon atoms ( V C ) 177 . This study also showed that significant change in E 0 occurs when the substituent at para ‐position of 6‐phenyl unit is changed, compared any other positions.…”
Section: Mesp As An Electronic Parametermentioning
confidence: 99%
“…The works of Suresh et al have given significant momentum to MESP applications and some of the several applications include comprehending substituent effect, lone pairs, resonance effect, inductive effect, non‐covalent bonding, and so forth. Recently, reduction potentials of cobalt complexes, fulvenes, and Fischer carbene complexes of chromium have been predicted with the use of MESP parameters. Recently, Anjali and Suresh interpreted the activation barriers of a large set of palladium (0) catalysts using the critical features of MESP distribution .…”
Section: Introductionmentioning
confidence: 99%